2020
DOI: 10.3201/eid2609.202144
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Description of Pregnant Women Infected with Severe Acute Respiratory Syndrome Coronavirus 2, France

Abstract: R ecent literature from China, Italy, and the United States suggests that pregnant women are not at higher risk for severe forms of coronavirus disease (COVID-19) from infection with severe acute respiratory syndrome (SARS) coronavirus 2 (SARS-CoV-2), contrary to what has been reported with SARS and MERS (1-3). Nevertheless, 3%-35% of infected pregnant women were hospitalized in intensive care units (ICUs) (2,4-7) and respiratory and hematology anomalies were described, just as in the nonpregnant infected popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 23 publications
2
33
0
6
Order By: Relevance
“…However, the participating centers involved did not drastically alter their management of patients with COVID-19 on the basis of pregnancy, except in cases of deterioration during the third trimester, when emergency delivery was sometimes needed to alleviate the additional physiological demands of pregnancy (data not indicated in this study). Based on this study and those of some other groups, 1 , 2 , 3 , 4 , 5 , 6 we advise clinicians to exercise prudence when planning the management of pregnant women diagnosed with COVID-19, particularly in the latter half of the pregnancy, when maternal risk of clinical decompensation and complications may be higher.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, the participating centers involved did not drastically alter their management of patients with COVID-19 on the basis of pregnancy, except in cases of deterioration during the third trimester, when emergency delivery was sometimes needed to alleviate the additional physiological demands of pregnancy (data not indicated in this study). Based on this study and those of some other groups, 1 , 2 , 3 , 4 , 5 , 6 we advise clinicians to exercise prudence when planning the management of pregnant women diagnosed with COVID-19, particularly in the latter half of the pregnancy, when maternal risk of clinical decompensation and complications may be higher.…”
Section: Discussionmentioning
confidence: 78%
“…Early reports focused solely on the fetal risks; however, the emphasis has correctly shifted toward maternal health. 2 , 3 , 4 , 5 , 6 A recent study reported a hospitalization rate of 52%, including a rate of 10% in intensive care unit (ICU) admission. 5 Nevertheless, the available literature is somewhat conflicting with some studies suggesting that pregnancy is not associated with markers of disease severity and others reporting worse outcomes.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 2 studies were excluded due to duplicity of data reporting. Out of 27 studies [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ], 16 studies were from China (14 were from Hubei province and 2 from Guangzhou) and 4 studies was from USA [ [44] , [45] , [46] , [47] ], 2 from France [ 48 , 49 ], 2 from Italy [ 50 , 51 ], 1 from UK [ 52 ], 1 from Spain [ 53 ], and 1 from Iran [ 54 ]. Of 27 studies, 4 studies (n = 233) also included a control group [ [38] , [39] , [40] , [41] ].…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, 169 articles were excluded for the following reasons: reviews and expert opinions (n = 55); case reports with less than 10 cases (n = 52); irrelevant studies (n = 17); studies without confirmation of COVID-19 by polymerase chain reaction (PCR) tests (n = 9); studies only including the infants born to mothers without confirmed COVID-19 (n = 7); and overlapping studies (n = 29). Hence, eleven studies on 9032 pregnant women with COVID-19 and 338 neonates were ultimately included for meta-analysis [17][18][19][20][21][22][23][24][25][26][27] . The main characteristics of the included studies are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%